THE EFFECT OF METACOGNITIVE STRATEGY ON STUDENTS GRAMMAR MASTERY - Sholihatul Hamidah Daulay; Mentari Octa (VISION, 2021)
This study was aimed to determine the grammar mastery of class XI students in understanding sentence material if conditional by using the metacognitive strategy learning method. Quantitative research is the type of research used and uses an experimental design. Researchers took data from MADRASAH ALIYAH YPP RIDHO ALLAH, PERLABIAN VILLAGE. The population in the school was 40 students from class XI-A and XI-B, each class has 20 students. The researcher gave a pretest before being given treatment and a posttest after treatment. Then the researcher analyzed the data using formulas and Microsoft Excel with a significance level of 0.05. Then the researchers obtained data from the study, namely the results of t count (8.55) > t table (1.69) which means Ha is accepted while Ho is rejected. The results of the study were obtained from the pretest and posttest scores of students from the experimental class and control class, where the posttest value in the experimental class was higher than the control class. It can be found that the Ha received has a significant influence on metacognitive strategies on the mastery of class XI Madrasah Alwasliyah YPP Ridho Allah students.